Exertional heat stroke leads to concurrent long‐term epigenetic memory, immunosuppression and altered heat shock response in female mice. (26th October 2020) - Murray, Kevin O.; Brant, Jason O.; Iwaniec, John D.; Sheikh, Laila H.; de Carvalho, Lucas; Garcia, Christian K.; Robinson, Gerard P.; Alzahrani, Jamal M.; Riva, Alberto; Laitano, Orlando; Kladde, Michael P.; Clanton, Thomas L.
Abstract : Key points: Exposure to exertional heat stroke (EHS) has been linked to increased long‐term decrements of health. Epigenetic reprogramming is involved in the response to heat acclimation; however, whether the long‐term effects of EHS are mediated by epigenetic reprogramming is unknown. In female mice, we observed DNA methylation reprogramming in bone marrow‐derived (BMD) monocytes as early as 4 days of recovery from EHS and as late as 30 days compared with sham exercise controls. Whole blood, collected after 30 days of recovery from EHS, exhibited an immunosuppressive phenotype when challenged in vitro by lipopolysaccharide. After 30 days of recovery from EHS, BMD monocytes exhibited an altered in vitro heat shock response. The location of differentially methylated CpGs are predictive of both the immunosuppressive phenotype and altered heat shock responses. Abstract: Exposure to exertional heat stroke (EHS) has been linked to increased susceptibility to a second heat stroke, infection and cardiovascular disease. Whether these clinical outcomes are mediated by an epigenetic memory is unknown. Using a preclinical mouse model of EHS, we investigated whether EHS exposure produces a lasting epigenetic memory in monocytes and whether there are phenotypic alterations that may be consistent with these epigenetic changes. Female mice underwent forced wheel running at 37.5°C/40% relative humidity until symptom limitation, characterized by CNS dysfunction. Results were compared with matched exercise controls at 22.5°C. Monocytes were isolated from bone marrow after 4 or 30 days of recovery to extract DNA and analyse methylation. Broad‐ranging alterations to the DNA methylome were observed at both time points. At 30 days, very specific alterations were observed to the promoter regions of genes involved with immune responsiveness. To test whether these changes might be related to phenotype, whole blood at 30 days was challenged with lipopolysaccharide (LPS) to measure cytokine secretion; monocytes were also challenged with heat shock to quantify mRNA expression. Whole blood collected from EHS mice showed markedly attenuated inflammatory responses to LPS challenge. Furthermore, monocyte mRNA from EHS mice showed significantly altered responses to heat shock challenge. These results demonstrate that EHS leads to a unique DNA methylation pattern in monocytes and altered immune and heat shock responsiveness after 30 days. These data support the hypothesis that EHS exposure can induce long‐term physiological changes that may be linked to altered epigenetic profiles. Key points: Exposure to exertional heat stroke (EHS) has been linked to increased long‐term decrements of health. Epigenetic reprogramming is involved in the response to heat acclimation; however, whether the long‐term effects of EHS are mediated by epigenetic reprogramming is unknown. In female mice, we observed DNA methylation reprogramming in bone marrow‐derived (BMD) monocytes as early as 4 days of recovery from EHS and as late as 30 days compared with sham exercise controls. Whole blood, collected after 30 days of recovery from EHS, exhibited an immunosuppressive phenotype when challenged in vitro by lipopolysaccharide. After 30 days of recovery from EHS, BMD monocytes exhibited an altered in vitro heat shock response. The location of differentially methylated CpGs are predictive of both the immunosuppressive phenotype and altered heat shock responses.